Implementasi Framework Laravel pada Aplikasi Pemesanan Jasa Photography menggunakan Metode Rapid Aplication Development - Amirul Amirul; Jaroji Jaroji; Muhammad Asep Subandri (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The advancement of technology in the field of photography has become an increasingly growing trend over time. In the context of Indonesia, the history of photography began in 1840, in line with the discovery of photography by Juriaan Munich, a Dutch media officer. Photography has been a part of people's lifestyle for centuries, ranging from the use of simple digital cameras to sophisticated devices that require specialized skills. Lensa Photography, as a photography studio in Bengkalis Regency, also faces challenges in the booking process. Manual processes through telephone or direct visits often result in scheduling errors. To address this issue, this study has successfully developed a website-based Lensa Photography booking system using the Laravel framework and the Rapid Application Development (RAD) development method. This booking system has successfully met its objectives by providing the following features, More efficient schedule management, Improved scheduling accuracy, Time and cost savings, Increased customer satisfaction, This booking system has been adopted by Lensa Photography and has provided significant benefits for the company, including, More organized and organized booking schedules, Reduced scheduling errors, More efficient booking time and costs, Increased customer satisfaction.